2003
DOI: 10.1097/00129492-200303000-00033
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Do Evaluations of Facial Paralysis by Physicians Coincide with Self-Evaluations by Patients: Comparison of the Yanagihara Method, the House-Brackmann Method, and Self-Evaluation by Patients

Abstract: Evaluations with the two systems correlated significantly with self-evaluations by patients on the whole. These two methods of evaluation are considered appropriate not only for physicians but also for patients. In contrast, some discrepancies were observed. This point should be taken into account in routine patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 4 publications
2
16
0
2
Order By: Relevance
“…Outro estudo (16) , por sua vez, avaliou a concordância da avaliação clínica e auto-avaliação realizada pelo paciente após a cirurgia de remoção do neurinoma do acústico. Utilizaram o Yanagihara System e House-Brackmann Grading System.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outro estudo (16) , por sua vez, avaliou a concordância da avaliação clínica e auto-avaliação realizada pelo paciente após a cirurgia de remoção do neurinoma do acústico. Utilizaram o Yanagihara System e House-Brackmann Grading System.…”
Section: Discussionunclassified
“…Ressaltam que freqüentemente são encontradas discordâncias entre a percepção da condição facial do ponto de vista médico e do paciente, além de haver, por vezes, discrepâncias entre a autopercepção do paciente e seu quadro clínico, o que pode influenciar nas decisões médicas, como intervenções cirúrgicas, e dificultar o processo terapêutico. Esses autores sugerem que a autoavaliação do paciente deve ser levada em conta na hora de definir os pontos a serem trabalhados em terapia, assim como são importantes a orientação e autoconhecimento do paciente quanto à sua face (10,16) .…”
Section: Introductionunclassified
“…To prevent observational bias, the study design included intraindividual (before versus after; ipsilateral versus contralateral) and interindividual (patients versus controls) observations. Facial expression was assessed by three board‐certified laryngology specialists using the Yanagihara scale and the House–Brackmann facial nerve grading scale . Because facial palsy is evaluated using a scale of 0–40 in the Yanagihara scale and a 6‐grade classification in the House–Brackmann scale, all statistical analyses were performed using scores from the Yanagihara scale.…”
Section: Methodsmentioning
confidence: 99%
“…Facial expression was assessed by three board-certified laryngology specialists using the Yanagihara scale 8 and the House-Brackmann facial nerve grading scale. [9][10][11] Because facial palsy is evaluated using a scale of 0-40 in the Yanagihara scale and a 6-grade classification in the House-Brackmann scale, all statistical analyses were performed using scores from the Yanagihara scale. Before starting the studies, use of the Yanagihara scale to assess paralysis was standardised among the three evaluators.…”
Section: Methodsmentioning
confidence: 99%
“…However, patient-reported data can be influenced by factors other than the direct effect of Botox. Standards for successful outcome may differ between physicians and patients 13 and may even differ between patients, 14 reducing measurement comparability. Concerns with the accuracy of self-reported data have been noted, 15 and studies have demonstrated that people inaccurately report even simple aspects of their recent experience.…”
mentioning
confidence: 99%